Eugenol protege contra a progressão dos danos neurodegenerativos em ratos hemiparkinsonianos - Vasconcelos, Carlos Franciney Moreira (2018)
Parkinson's disease (PD) is a multicentric neurodegenerative disorder that affects the central nervous system and is characterized primarily by the loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). Its etiology is not clear, but several factors have been identified as indicators of its pathophysiology, such as neuroinflammation, mitochondrial dysfunction, oxidative stress and abnormal protein aggregation. Currently the treatments for PD are restricted to symptomatic relief, mainly for motor symptoms, and are not effective in preventing the progression of the disease. In addition, current therapy based on endogenous drug dopamine replacement, whose "gold standard" is Levodopa (L-DOPA), in the treatment of PD may trigger adverse side effects. Eugenol is a phenylpropanoid that has been widely studied due to its anti-inflammatory, anti-excitotoxic and antioxidant activities. In this way, it presents itself as a promising neuroprotective agent and may provide new therapeutic intervention strategies for the treatment of PD. The aim of this study was to investigate the effects of eugenol and / or L-DOPA on neurotoxin 6-OHDA induced by neurotoxin 6-OHDA model, through neurochemical and neurobehavioral analyzes. To evaluate the neuroprotective potential of eugenol, wistar rats (250-300 g) were used, which were submitted to the PD model by intra-atrial injection of 6-OHDA (21 μg / animal) and then treated with L-DOPA (25 mg / kg) or the association between the compounds (Eug 10 mg / kg + LD 12.5 mg / kg) orally for 14 days . On the last day of treatment, the animals were submitted to specific behavioral tests (Open field, Rota-rod and Rotational test induced by apomorphine) and, after euthanasia and dissection of the cerebral areas (ipsi and contralateral striatum, Hippocampus and Prefrontal Cortex ), the neurochemical analyzes were performed (determination of MDA, nitrite / nitrate and GSH levels). Additionally, the effect of these treatments on the body mass gain was evaluated. The results showed that eugenol had a dose-dependent effect on recovery of motor damage and spontaneous exploratory activity, as well as on mass gain in animals. In addition, the most effective dose (10 mg / kg) was able to reduce nitrite / nitrate and MDA levels, in addition to recovering the endogenous levels of GSH. The association between eugenol and L-DOPA, in turn, was shown to be more effective in some neurobehavioural parameters and in body mass gain, besides promoting an increase in GSH levels in all brain areas analyzed in relation to the group treated only with L-DOPA. However, these did not differ in the levels of MDA and nitrite / nitrate, in relation to the hemiparkinsonian animals. Thus, a neuroprotective effect of eugenol against motor and neurochemical disorders associated with the 6-OHDA-induced hemiparkinsonism model was observed. Additionally, the association between eugenol and L-DOPA was promising when compared to conventional treatment, but did not differ from this in the reduction of nitrosative stress and lipid peroxidation.